ECONOMIC AND ENVIRONMENTAL ASPECTS OF STUDYING THE STABILITY OF AGROECOSYSTEMS UNDER CONDITIONS OF RISING ANTHROPOGENIC PRESSURE - Khalishkhova; Temrokova; Marzhokhova; Bagova; Babaeva (Revista Inclusiones, 2020)
Ensuring the sustainable development of agroecosystems requires the study of problems and antinomies of interaction between territorial production systems and agroecosystems. The main goal of the research within the framework of the article is to identify significant contradictions in the interaction of the indicated systems, as well as the paradoxes of their functioning, which will allow us to formulate conceptual provisions for the sustainable environmental and economic development of agricultural territories.